Gastroenterologists’ perceived barriers to optimal pre-colonoscopy bowel preparation: Results of a national survey - Hillyer, Grace Clarke (2012)
Poor quality bowel preparation has been reported in almost one-third of all colonoscopies. To better understand factors associated with poor bowel preparation, we explored perceived patient barriers to optimal bowel preparation from the perspective of the gastroenterologist. A random sample of physician members of the American College of Gastroenterology was surveyed via the internet and postal mailing. Demographic and practice characteristics, and practice-related and perceived patient barriers to optimal bowel preparation were assessed among 288 respondents. Lack of time, no patient education reimbursement and volume of information were not associated with physician level of suboptimal bowel preparation. Those reporting ≥10% suboptimal bowel preparations were more likely to believe patients lack understanding of the importance of following instructions; have problems with diet; and experience trouble tolerating the purgative. Bowel preparation instruction communication and unmet patient educational needs contribute to suboptimal bowel preparation. Educational interventions should address both practice and patient-related factors.